(untitled) (Journal of Universal Excellence, 2026)
Research question: Is the model of the Control theory of systems, after ten years, it is still a useful model for the organisation of the health care System in Slovenia? Purpose: Examine whether abnormalities of the functioning of the health care System less, than in the time when the model of the Control theory Systems appeared. Method: We used a comparative analysis of the theoretical and practical knowledge in two different periods. Results: We find that the health policy problem in the health care System in Slovenia tracks, are identified as critical for the implementation of the reform, the latter, however, mainly carried out with some legal changes and new capital injections in the health care System in Slovenia, without prior purification of the organizational anomaly in them. Organization: Use the model in health care organizational systems - become a modern and efficient organisation. Society: Well-organized and effective health care organizational systems - greater social prosperity. Orginality: The model is still unique and suitable for use.